(untitled) (Research, Society and Development, 2022)
There are few studies on anxiety in the Brazilian market, which compromises the diagnosis and conduct of prospective studies to clarify risk factors and possible outcomes. Thus, it is interesting to carry out the present study in order to better understand the aspects related to anxiety triggers. To analyze the scientific production related to the triggering factors of anxiety in today’s society. This is an integrative review of studies published between 2009 and 2019, available in Portuguese and English. A survey was carried out in the Lilacs, PubMed and SciELO databases. For methodological quality analysis, the adapted Critical Appraisal Skill Program (CASP) and the adapted Agency for Healthcare and Research and Quality (AHRQ) were used. Among the triggering factors, occupational stress has gained prominence on the national scene, being recognized as a major anxiety factor in the 21st century. The endocrine system is the major pathophysiological influencer related to the triggering of anxiety. Age and sex were the main demographic factors, the articles evaluated that, on average, individuals develop anxiety at age 22. In addition, females are more affected. Most studies evaluated the socioeconomic level using variables such as employment, education and family income. The genetic component, in fact, can be recognized as a predisposing factor, however, further studies are needed in order to clarify points that are still unknown. In fact, socioeconomic aspects, among others, were the main contributor to anxiety, being the main focus of the review studies. The included studies suggested that demographic, socioeconomic, pathophysiological and genetic factors would be the predictors of anxiety disorders.